What drives purchase intention for paid mobile apps? – An expectation confirmation model with perceived value - Hsu, Chin-Lung; Lin, Judy Chuan-Chuan (Electronic commerce research and applications, 2015)
•Confirmation was positively related to perceived value and satisfaction.•Free alternatives to paid apps negatively affects a user’s intention to purchase.•Increasing value-for-money will increase intention to purchase apps.•Intention to purchase apps was different between users and potential users. While many reports predict huge growth potential for the mobile application (app) market, little is known about user intention to purchase paid apps. This study amends the expectation confirmation model and incorporates app rating, free alternatives to paid apps and habit as belief-related constructs to predict user behavior. The proposed model was empirically evaluated using a survey of 507 respondents about their perceptions of app usage. The results indicated that confirmation was positively related to perceived value and satisfaction. Value-for-money, app rating and free alternatives to paid apps were found to have a direct impact on intention to purchase paid apps. Specifically, there was a significant difference between potential users and actual users. The results may provide further insights into app marketing strategies.